Stress-based form-finding of gridshells for Wire-and-Arc Additive Manufacturing considering overhang constraints. (15th March 2023) - Bruggi, Matteo; Laghi, Vittoria; Trombetti, Tomaso
Abstract: The design of spatial truss networks for fabrication using Wire-and-Arc Additive Manufacturing (WAAM) is addressed, combining funicular analysis and optimization. At first, a characterization of the structural behavior of the printed bars is provided based on available experimental tests. Interpolation laws are given both for the yielding stress and the critical stress in compression, depending on the printing direction. Then, dealing with networks with fixed plan projection, a minimization problem is formulated in terms of any independent subset of the force densities and of the height of the restrained nodes. The maximum value of the ratio of the axial force in each branch of the network to the relevant yielding/critical force is adopted as objective function. Local enforcements are prescribed to set lower and upper bounds for the vertical coordinates of the nodes and to control the overhang angle with respect to the vertical direction in the AM process. Gridshells retrieved by the proposed approach are presented and compared to those found when seeking for spatial networks with minimum horizontal reactions, disregarding or considering overhang constraints. Peculiar features of the achieved layouts are pointed out. Highlights: Mechanical properties of WAAM-printed bars are interpolated as a function of the build angle. The Perry–Robertson capacity formula fits well experimental data in compression. Overhang constraints are accounted for when designing optimal funicular networks. Problems of minimum thrust, and min–max of the critical/yielding forces are solved. Form and force variations arise depending on the selected objective function.